ANALISIS YURIDIS PEMBAYARAN GANTI RUGI SEBESAR SETENGAH SISA UPAH SAMPAI BERAKHIRNYA PERJANJIAN KERJA WAKTU TERTENTU - Widyowati, Wulandari; Rusdiana, Emmilia (Universitas Negeri Surabaya, 2020)
The problem in Indonesia is not detached from the working relationship. Problems that often arise from the relationship of employment are termination of employment (LAYOFFS or PHK). In the case of LAYOFFS, employers are obliged to give severance money or damages and/or other rights. In this research the author raised the topic of the issue of the Supreme Court's Decision Number 778 K/Pdt.Sus-PHI/2018 regarding the payment of damages amounting to half the remaining wage to the end of the specific time working agreement (PKWT), while article 62 of Law Number 13 of 2003 on employment contained provisions that the parties conduct LAYOFFS prior to the end of the PKWT then the party shall be liable to pay damages to the other party of wages of workers until the deadline expires. The research aims to analyse the Supreme Court's decision on the payment of half the remaining wages for compensation to the end of the PKWT based on prevailing laws and regulations. As for the research method used is normative juridical using a statutory approach and a case approach. The results showed that the judgment of the Supreme Court Judge in the Supreme Court's Decision Number 778 K/PDT. Sus-PHI/2018 regarding the payment of half the remaining damages to the end of the PKWT is not appropriate because the entrepreneur is only charged a compensation of half the remaining wage until the end of the PKWT which should compensate the remaining wage to the end of the PKWT.